Robot-assisted Treatment of Epigastric Hernias With a Suprapubic Approach. Issue 5 (23rd October 2021) - Pini, Ramon; Di Giuseppe, Matteo; Toti, Johannes M.A.; Mongelli, Francesco; Marcantonio, Maria; Spampatti, Sebastiano; La Regina, Davide
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Robot-assisted ventral hernia repair has shown itself to be feasible and safe in abdominal wall surgery. Presently, the ports are placed laterally to meet the distance from the fascial defect. The aim of our study is to report our experience of epigastric hernia treatment with trocar insertion in the suprapubic region. Materials and Methods: On a prospectively collected dataset on robot-assisted surgery, patients treated for epigastric hernias with suprapubic approach were identified. Demographic and clinical data were collected and analyzed. Results: Twelve patients were selected. Median age was 58.5 years [interquartile range (IQR): 47.8 to 67.3 y]; 4 patients were male (33.3%) and the median body mass index was 23.9 kg/m 2 (IQR: 22.3 to 26.2 kg/m 2 ). All patients were referred to surgery because of pain. The median measure of the hernia defect was 30 mm (IQR: 13.75 to 31.0 mm); median larger mesh diameter was 13.5 cm (IQR: 9.5 to 15.0 cm); and median operative time was 136.5 minutes (IQR: 120.0 to 186.5 min). No intraoperative complication or conversion to open surgery occurred. Postoperatively, 2 patients presented a seroma and median length of hospital stay was 2.0 days (IQR: 1.75 to 3 d). No case of hernia recurrence was recorded at a mean follow-up of 11.2 months (range: 4 to 29 mo). Conclusions: In the robot-assisted treatment of hernias of the epigastric region, a suprapubic port placement can be considered instead of a lateral one to have a better field overview, especially in subxiphoid hernias. Further studies are needed to assess the benefits and limitations of such technique.